Development of Herbarium-Based Learning Media for the Classification of Living Organisms in Grade VII at Pondok Pesantren Darunnadwah - Riska Nabila (MultiTech Publisher, 2023)
The use of instructional media in teaching Natural Sciences has a significant impact on student engagement, concept comprehension, motivation, and learning outcomes. This research aims to develop herbarium-based instructional media that can support the learning of classifying living organisms for seventh-grade students at Pondok Pesantren Darunnadwah. The research method employed is Research & Development (R&D) using the ADDIE model, which encompasses three main stages: Analysis, Design, and Development. The validation results by the IPA teacher indicate a score of 80% (very worthy), and based on student responses during the trial of the herbarium media, an average score of 89.5% (very worthy) was obtained. Herbarium media does not require further revision.